Effect of natural products on the pathogenesis of acute experimental pancreatitis - Szabolcs Annamária; Takács Tamás (2008)
Acute pancreatitis is a disease with high mortality and without efficient treatment. The aim of our study was to demonstrate the effects of three natural substances with antioxidant and anti-inflammatory properties on the severity of acute experimental pancreatitis. Besides the regulation of the circadian rhythm the pineal product melatonin has recently been shown to exhibit strong antioxidant as well as anti-inflammatory effects in various organs like the brain, heart, liver, retina and the gut. Melatonin can directly detoxify free radicals; it influences the antioxidant function of scavenger enzymes and depresses the synthesis of inflammatory cytokines through the inhibition of the transcription factor NF-kappa B. Resveratrol is a plant-derived phytoalexin used in the traditional Chinese medicine as a drug against inflammation, allergy and hyperlipidemia. It exerts beneficial effects in several organs like heart, brain, lung and intestines by el iminating free radicals, inhibiting platelet aggregation, endothelial activation and the activation of NF-kappa B. As a high amount of resveratrol is present in red wine, it is possible that the substance is responsible for the “French paradox” describing the protective effects of red wine consumption. Zerumbone is a sesquiterpenoid found in large amounts in the rhizome of Zingiber zerumbet, a plant traditionally used as a condiment and in the South-east Asian countries as a drug for the treatment of swellings, sores, loss of appetite, worm infestation, toothache and indigestion. Besides its antioxidant effects, the molecular background of the action of zerumbone is probably mediated by the inhibition of NF-kappa B leading to decrease of IL-1β, TNF-α levels and the reduction of the de novo synthesis of iNOS and COX-2. The effects of these three substances on acute pancreatitis were examined in different experimental setting. Our results lead to the conclusion that the pineal product melatonin has a moderate impact on the pancreas, but due to its antioxidant qualities it can exert a protective effect in the liver of animals with acute necrotizing pancreatitis. The beneficial pancreatic effects of resveratrol in acute edematous pancreatitis are presumably mediated by the intrinsic antioxidant effect of resveratrol or by an NF-κ B-independent anti-inflammatory mechanism. In contrast to this, the observed antioxidant and anti-inflammatory effects of isolated zerumbone are likely to be mediated through the inhibition of NF-κ B activation.
Disszertacio
Keywords: elméleti orvostudományok